2019
DOI: 10.1161/jaha.119.012670
|View full text |Cite
|
Sign up to set email alerts
|

Age‐Dependent Impairment in Endothelial Function and Arterial Stiffness in Former High Class Male Athletes Is No Different to That in Men With No History of Physical Training

Abstract: BackgroundPhysical activity is generally considered to exert positive effects on the cardiovascular system in humans. However, surprisingly little is known about the delayed effect of professional physical training performed at a young age on endothelial function and arterial stiffness in aging athletes. The present study aimed to assess the impact of long‐lasting professional physical training (endurance and sprint) performed at a young age on the endothelial function and arterial stiffness reported in older … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
33
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 27 publications
(36 citation statements)
references
References 63 publications
2
33
0
Order By: Relevance
“…The interactions between androgens and inflammation may be influenced by adipose tissue because it is well known that the inflammatory process results from an imbalance between the pro- and antioxidant systems often related to dysfunctional adipose tissue ( 10 ). We have recently demonstrated that the BMI and body fat percentage correlated positively with the inflammatory and oxidative stress markers in men ( 11 ), which could explain the age-related increase in inflammation and oxidative stress that led to a decline in endothelial function and an increase in arterial stiffness. In addition, Bobjer et al.…”
Section: Introductionmentioning
confidence: 99%
“…The interactions between androgens and inflammation may be influenced by adipose tissue because it is well known that the inflammatory process results from an imbalance between the pro- and antioxidant systems often related to dysfunctional adipose tissue ( 10 ). We have recently demonstrated that the BMI and body fat percentage correlated positively with the inflammatory and oxidative stress markers in men ( 11 ), which could explain the age-related increase in inflammation and oxidative stress that led to a decline in endothelial function and an increase in arterial stiffness. In addition, Bobjer et al.…”
Section: Introductionmentioning
confidence: 99%
“…Although serum sodium concentration is inversely associated with circulating CD34-positive cell levels among subjects without hypertension, no data were available for the evaluation of endothelial function. As aging is the main contributing factor to decline in endothelial function 44 , further analyses that include endothelial function-related data such as flow-mediated dilation (FMD) will be necessary. Unknown confounding factors such as medication status and duration of medication for hypertension, diabetes, dyslipidemia, inflammatory disease, and thyroid disease, could influence the present study.…”
Section: Discussionmentioning
confidence: 99%
“…Majerczak and colleagues showed that both the amount of oxidative stress by lipid peroxidation and glycocalyx shedding by syndecan-1 and heparan sulfate release in circulation were significantly reduced, while the enzymatic antioxidative defence by superoxide dismutase (SOD) in muscle was increased after 20 weeks of moderate-intensity endurance training 13 . However, analysis of parameter relationships was not performed in the aforementioned study and recent reports stated no change of glycocalyx integrity with exercise training 14 or between moderately trained and untrained participants 15 .…”
Section: Introductionmentioning
confidence: 93%